Optimization of chitosan, sodium carboxy methyl celulose and magnesium stearat as mucoadhesive system in captopril tablet - Irawan, Eka Deddy; Fudholi, Achmad (INDONESIAN JOURNAL OF PHARMACY, 2009)
Captopril is an angiotensin-converting enzyme inhibitor (ACE inhibitor) used for the treatment of hypertension and some types of congestive heart failure. It has been reported that the duration of antihypertensive action after a single oral dose of captopril is only 6â8 h. Captopril is most stable at acidic condition and as the pH increases, it becomes unstable and undergoes a degradation reaction. These indicates a promising potential of the captopril mucoadhesive system as an alternative to the conventional dosage form. The objective of the current study was to find an optimum formula of mucoadhesive tablet for captopril using factorial design. Tablets were evaluated for mucoadhesive strength and drug release profile. The studies were perfomed to establish composition of chitosan, sodium CMC and Mg stearat. Such composition could produce mucoadhesive strength with a zero order release kinetics. A 23 factorial design has been applied to systematically optimize the formula. The amounts of chitosan (XA), sodium CMC (XB), and Mg stearat (XC) were selected as independent variables. Mucoadhesive strength and dissolution efficiency (DE480) were selected as dependent variables. According the contour plot suggested that optimum formula will be reach mucoadhesive strength (26-30 g) and DE480 (â¥70 %) chitosan at low to middle level (20-35 mg), sodium CMC at middle to high level (150-200 mg), and Mg stearat at low to middle level (4-6 mg).Key words : mucoadhesive, factorial design, DE480 , chitosan, CMC Na, Mg stearat, contour plot